Pengembangan Media Pembelajaran Matematika berbantuan Chatbot (WhatsAuto) WhatsApp pada Materi Barisan dan Deret untuk Siswa Kelas X - Afsyah, Moh. Zaini; Nugraha, Aldila Wanda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
To foster students' understanding of concepts in learning, one of them is by using appropriate and easy-to-use learning media, such as WhatsApp Chatbot (WhatsAuto) media. The use of WhatsApp Chatbot (WhatsAuto) media developed is expected to make it easier for students to understand the concept of row and series material and provide convenience in the learning process for teachers both online and offline, anywhere, anytime with an internet connection. This study aims to determine the validity and practicality of mathematics learning media assisted by Chatbot (WhatsAuto) WhatsApp on the material of rows and series for class X students at SMA Negeri 1 Kalidawir. This research uses the Borg and Gall development model with 4 stages, namely Research and information gathering; Planning; Develop preliminary from of profuct; Preliminary field testing. The results of the WhatsApp Chatbot (WhatsAuto) media research developed meet the criteria of highly valid, namely media experts showing a percentage of 94%, material experts 100%, practitioners 96%, and students showing a percentage of 88% with very practical criteria. It can be concluded that the Chatbot (WhatsAuto) WhatsApp media developed is very valid and very practical to use in the process of learning mathematics on the material of rows and series in class X.